1962
DOI: 10.1002/app.1962.070061912
|View full text |Cite
|
Sign up to set email alerts
|

Sur la déagradation thermique du chlorure de polyvinyle. II. Etudes cinéatiques sous atmosphéare inerte

Abstract: Le present travail a pour but de preciser, dans la mesure du possible, et par Btude cinbtique, les causes et les mecanismes de la degradation thermique du chlorure de polyvinyle (CPV). La complexite des phdnomenes impliques a conduit les aut,eurs B operer dans les conditions experimentales les plus simples: sous atmosphere inerte d'azote purifi6 et avec un produit commercial debarass6 au maximum des impuretes qu'il pouvait contenir. MATERIAU L'echantillon de polymere faisant l'objet de cette Btude est un chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1966
1966
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The activation energies calculated for the Geon resin, the copolymer, and the emulsion PVC are 41. 8 have generally been reported for PVC from dehydrochlorination stud-As stated before, the slope of the curve in region I1 is generally zero and, therefore, the rate constant is zero. This being the case, it means either no reaction is occurring or that the reaction that is occurring does not have a significant affect on the shear viscosity.…”
Section: Io-'mentioning
confidence: 61%
“…The activation energies calculated for the Geon resin, the copolymer, and the emulsion PVC are 41. 8 have generally been reported for PVC from dehydrochlorination stud-As stated before, the slope of the curve in region I1 is generally zero and, therefore, the rate constant is zero. This being the case, it means either no reaction is occurring or that the reaction that is occurring does not have a significant affect on the shear viscosity.…”
Section: Io-'mentioning
confidence: 61%
“…The UV-VL analyses of low conversion products revealed that the number of conjugated C-C double bond has a distribution ranging from 2 to 15. [13][14][15][16][17] In the case of chemical degradation of PVC in solutions by organic or inorganic bases, such as DMF or potassium t-butoxide, the polyene distribution was similar to that found in thermally or radiolytically degraded PVC.5-9J1J2 Since the solubility of highly degraded PVC is very low, the UV-VL analyses have been limited to the low conversion products.…”
Section: Dehydrochlorination Of Pvc Filmmentioning
confidence: 98%
“…Therefore, the rate constant of elimination of successive halogen atoms increases considerably. This is also favored by the fact that proton-donating additives, e.g., halogen acids, catalyze the thermal HC1 elimination [188][189][190][191][192], since the attack of protons at labile chlorine atoms in a-position relative to the arising system of conjugated bonds, weakens its C-C1 bonds to a high degree. Finally, the emerging conjugated system can catalyze the process for reasons which will be discussed later.…”
Section: Polymeranalogous Reactionsmentioning
confidence: 99%